MEKANISME PEMBERHENTIAN HAKIM MAHKAMAH KONSTITUSI SEBELUM HABIS MASA JABATANNYA - Purnamawati, Evi (Solusi, 2024)
This research uas used normative jusdical about Constitutional Court Judges to be respectfully dismissed according to Law No. 7 of 2020 concerning the Constitutional Court and what is the legal meaning of Constitutional Court Decisions which are Final and Binding. The results of research on the dismissal of constitutional judges in Law 24/2003 as amended into Law Number 7 of 2020 concerning the Constitutional Court Become a Law and in more detail regulated in Constitutional Court Regulation Number 4 of 2012 concerning rocedures for Dismissing Constitutional Judges ("PMK 4 /2012”). Constitutional judges are honorably dismissed for the following reasons: death, resignation at their own request submitted to the Chief Justice of the Constitutional Court, being 70 (seventy) years old; removed; or, hysical or mental illness continuously for 3 (three) months so that he cannot carry out his duties as proven by a doctor's certificate. The decision of the Constitutional Court, which is final and binding, contains 4 (four) legal meanings, namely: First, to create legal certainty as soon as possible for the parties to the dispute. Second, the existence of the Constitutional Court as a Constitutional Court. Third, it is meaningful as a form of social control carried out by the Court. Fourth, as the sole guardian and interpreter of the constitution.